Os impactos do turismo no município de Santo Amaro - MA antes e depois da construção da rodovia MA-320: uma análise sob a percepção dos atores sociais - Rocha, Michelle Santos (2022)
This study analyzes the impacts of tourism in the municipality of Santo Amaro MA before and after Highway MA 320 from the perception of its social actors, reflecting on the main implications for local development. It is based on the Dialectical Historical Materialism method, as it analyzes the contradictions of the object studied. It contextualizes the dynamics of tourism with its history, typology and sustainability, based on the various impacts that are attributed to this activity in the economic, sociocultural and environmental spheres. It also indicates an understanding of the processes through the perception of the social actors of government, market and civil society about the reality of this region, considering the role played by each of them in the organization of tourism. In this way, it characterizes the aforementioned municipality by talking a little about the Conservation Unit and with general information about its history, economy, heritage and tradition, emphasizing tourist relations. Then, he talks about community-based tourism that already occurred spontaneously and about what is currently being implemented in contrast to mass tourism caused after the opening of the road. There are also two projects that aim to install large tourist enterprises in the municipality with the ease of access provided by the MA-320 road. In this light, the discussion is centered on the positive and negative impacts of tourism on the perception and evaluation of these actors involved